Succinate dehydrogenase B‐deficient renal cell carcinoma: A case report with novel germline mutation. Issue 11 (28th September 2017) - Iwashita, Hiromichi; Okudela, Koji; Matsumura, Mai; Yamanaka, Shoji; Sawazumi, Tomoe; Enaka, Makiko; Udaka, Naoko; Miyake, Akio; Hibiya, Takashi; Miyake, Noriko; Matsumoto, Naomichi; Makiyama, Kazuhide; et al.
Abstract : Succinate dehydrogenase‐deficient renal cell carcinoma (SDH‐deficient RCC) is a newly introduced histological type of RCC, which is caused by loss of subunit genes of SDH. It is known to frequently demonstrate familial occurrence and be frequently associated with gastrointestinal stromal tumors and paraganglioma. To date, only 53 cases have been reported. Here, we present an additional case of SDH‐deficient RCC occurring in a 40‐year‐old female. The tumor was histologically biphasic, consisting of tubular and solid architectures. The tumor cells possessed oval nuclei with small nucleoli, and an eosinophilic granular cytoplasm with occasional vacuoles. These cells completely lost the immunohistochemical expression of B subunit of SDH (SDHB). Consequently, the tumor was diagnosed as SDHB‐deficient RCC. We identified a novel germ line mutation of the SDHB gene, and also confirmed a hemizygous deletion of the wild‐type allele in the tumor cells. To define the pathological characteristics of SDH‐deficient RCC, precise diagnosis and accumulation of more cases are required.